The Influence of Language Learning Strategies on Students’ Linguistic Competence - Maulina Nabila; Cecep Agus (Jurnal Impresi Indonesia, 2025)
Linguistics, as the scientific study of language, provides a fundamental framework for understanding how learners acquire and develop their linguistic competence. However, many students still face difficulties in achieving adequate mastery of language skills, which can hinder their academic performance. This study aims to examine the influence of language learning strategies on students’ linguistic competence. A quantitative approach was employed, utilizing a survey design with a sample of undergraduate students from the English Department. The data were collected through a structured questionnaire based on Oxford’s Strategy Inventory for Language Learning (SILL) and a linguistic competence test covering phonology, morphology, syntax, and semantics. The results of regression analysis indicate that language learning strategies have a significant positive effect on students’ linguistic competence, with metacognitive and cognitive strategies showing the strongest influence. These findings suggest that effective use of language learning strategies enhances students’ understanding of linguistic principles and improves their overall performance in linguistics courses. The study highlights the pedagogical implication that lecturers should integrate strategy-based instruction in the classroom to optimize students’ linguistic development.